Unveiling the Use of Networked Ontologies to Develop a Supporting Tool for UX Evaluation in an Immersive Context - Costa, Simone Dornelas (2025)
Immersive technologies have emerged as a new type of interactive system that aims to provide users with immersive experiences. They have been adopted in various fields and are gradually becoming part of our lives. UX is a key quality attribute to evaluate or model such experiences. However, when it comes to immersive experiences, evaluating UX is particularly challenging because the user should not be interrupted to provide feedback. Aiming at giving a step to address this issue, we have explored using ontologies from an ontology network to support evaluating immersive experiences. In this work, we adopted the Human-Computer Interaction Ontology Network (HCI-ON) and used an extract containing concepts from some of its networked ontologies to develop the User eXperience evaluation based on Ontology Network (UXON), an ontology-based tool that supports UX experts evaluating immersive experiences based on data recorded in interaction logs. HCI-ON is a framework for organizing knowledge of the HCI domain, offering a general understanding of the field, regardless of specific solutions. UXON was used to evaluate the UX of Compomus, an immersive application that supports collaborative music composition. UXON extracts data from the application interaction logs, calculates UX metrics, and provides consolidated data and information in graphs and tables. We conducted a study and collected feedback from the UXON developer and three UX experts who used the tool. Results showed that using networked ontologies to develop a tool to support UX evaluation is feasible and valuable. In summary, the ontologies helped at the conceptual level by offering a basis to define the system's structural model and at the implementation level by assigning semantics to data to make inferences about UX. Based on the UX experts' perceptions, UXON was considered a promising system, beneficial, helpful, and easy to use. The conceptualization used to develop UXON was evaluated by HCI experts and it was considered adequate and understandable, having the potential to be used by other people to solve HCI evaluation problems.